Enhancing Early Child Development A Handbook for Clinicians - Sinno, Durriyah; Charafeddine, Lama.; Mikati, Mohamad; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Early childhood development refers to the skills that children acquire within their first five years of life, which lay the foundation for future learning. Children need care and support to stimulate their growth and healthy development. The stimulation of language, understanding, personal, social and motor skills of the child are important at an early age and it is one of the primary physicians$1 (Bresponsibilities to give proper advice to parents on how to promote their children$1 (Bs physical and mental development. Enhancing Early Child Development: A Handbook for Clinicians is a quick reference guide for pediatricians, clinicians, and pediatric nurse practitioners that aims at promoting early stimulation and intervention for optimizing development of normal children as well as children with cerebral palsy and autism. Designed to be used in daily practice, this book will provide counsel for clinicians, parents and caregivers and advise them on the appropriate methods to enhance their child$1 (Bs development at different ages based on their health condition. In addition, Enhancing Early Child Development: A Handbook for Clinicians, incorporates a summary of the manual entitled "Counsel the Family on Care for Child Development" developed by UNICEF and WHO, which addresses child development in low resource countries.s
Keywords: Medicine; Family medicine; Pediatrics; Emergency medicine; Developmental psychology; Medicine & Public Health; Pediatrics; Primary Care Medicine; General Practice / Family Medicine; Child and School Psychology